Scope of the lex successionis and its coordination with the lex rei sitae-lex registrationis: a purpose of the legacies by vindication - Castellanos Ruiz, Esperanza (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Regulation (EU) no. 650/2012 of the European Parliament and the Council of 4 July 2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of succession and on the creation of a European Certificate of Succession is one of the most important results hitherto achieved for codifying private international law which the European Union. Recognizing the effort of the Member States to coordinate the unification of the rules of private international law in this area, its application is not exempt from problems with other areas that directly affect the regulation of the succession of a person, as happens for example with the regulation of property law that may affect the inheritance assets. Recognition of foreign property law may create problems in light of a Member State’s numerus clausus of property rights and differing land registration regimes. The study of the matters governed by the lex successionis, listed in article 23.2 ESR, must be done taking into account article 1.2 ESR, setting out the issues which are excluyed from the lex successionis scope. Often the exclusion or inclusion of particular matters from or within the scope of application of the lex successionis are two sides of the same coin. In other words, article 1.2 ESR governs the scope of application in a negative sense and article 23.2 ESR in a positive sense. However, the collision arises in relation to the application of the lex rei sitae to certain inheritance questions that are included in the scope of application of lex successionis to which the two Acts must be applied cumulatively. This is what happens with the regulation by lex successionis of the transfer to the heirs and, as the case may be, to the legatees of the assets, rights and obligations forming part of the estate, including the conditions and effects of the acceptance or waiver of the succession or of a legacy, according to letter e) of art. 23.2, bearing in mind that the letters k) and l) of art. 1.2, exclude from the application of the succession law the nature of rights in rem; and any recording in a register of rights in immovable or movable property, including the legal requirements for such recording, and the effects of recording or failing to record such rights in a register; issues that, in most cases, are subject to the lex rei sitae or lex registrationis. This conflict of laws is what led to the first decision of the CJEU on the Succession Regulation: Judgment of the Court of Justice of the European Union, Second Chamber, of October 12, 2017: Kubicka.
Keywords: International succession; lex successionis; lex rei sitae; lex registrationis; the scope of the aplicable law; rights in rem; property rights; legatum per vindicationem y per damnationem